Foreign subsidiary CSR as a buffer against parent firm reputation risk - ZHOU, Nan (Institutional Knowledge at Singapore Management University, 2020)
This study examines the influence of parent firm reputation risk on the level of corporate social responsibility activities of foreign subsidiaries. We first argue that a strong reputation risk spillover occurs from parent firms to their foreign subsidiaries due to the high visibility of multinationals, the control of parent firms over their subsidiaries, and the liability of foreignness associated with foreign firms in host countries. Then, we argue that subsidiaries may resort to CSR in their host country to reduce the spillover effect. Thus, we hypothesize a positive relationship between parent firm reputation risk and foreign subsidiary CSR activities. Moreover, we explore several contingency factors at both the parent firm and subsidiary levels that affect the extent of spillover and the need for subsidiaries to use CSR as a buffer against parent firm reputation risk. We find that the positive relationship between parent firm reputation risk and foreign subsidiary CSR activities is weaker for foreign subsidiaries that directly report to the parent firm, with longer operations in the host country and larger institutional distance between host and home countries. Using a unique sample of subsidiaries of large multinationals in China from 2009 to 2016, we find general support for our arguments.